Uni- and biaxial impact behaviour of double-gated nanoclay-reinforced polypropylene injection mouldings - Pettarin, Valeria (2013)
Documento submetido para revisão pelos pares. A publicar em Polymer Engineering & Science. ISSN 1548-2634.